PERKEMBANGAN SASTRA ARAB PADA MASA JAHILIYAH - Jauhari, Qomi Akit (Jurnal Bahasa Lingua Scientia, 2011)
The Arabic literary work is very famous for its beauty. Even, its beauty is incomparable to the literary work of other languages. Yet, not all Moslems know vividly the history of the Arabic literature. To understand the Arabic literary work, a Moslem must master the Arabic language first. This article is aimed at explaining the development of the Arabic literature especially before Mohamed?s prophecy era.